2021
DOI: 10.1021/acs.jafc.1c00140
|View full text |Cite
|
Sign up to set email alerts
|

The Crosstalk between Autophagy and Apoptosis Is Necessary for Myogenic Differentiation

Abstract: Skeletal muscle is a major organ in animals, which constitutes over 40% of livestock body weight, and plays a critical role in metabolism and homeostasis in an organism. Autophagy and apoptosis are two major processes to determine cell fate. Recently, the importance of autophagy and apoptosis in myogenesis has been identified; however, their crosstalk is not well defined. In this study, we aimed to explore the relationship between apoptosis and autophagy during myogenic differentiation. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Autophagy and apoptosis coexist in early muscle injury throughout regeneration because the former is responsible for cell reprogramming by regulating cytoplasmic remodelling, while the latter eliminates defective cells that do not have differentiation potential [ 49 , 50 ]. The crosstalk between apoptosis and autophagy determines the balance of cell survival and death, allowing SCs to differentiate normally [ 51 ]. However, improper autophagy and apoptosis hamper myotube formation and muscle regeneration [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy and apoptosis coexist in early muscle injury throughout regeneration because the former is responsible for cell reprogramming by regulating cytoplasmic remodelling, while the latter eliminates defective cells that do not have differentiation potential [ 49 , 50 ]. The crosstalk between apoptosis and autophagy determines the balance of cell survival and death, allowing SCs to differentiate normally [ 51 ]. However, improper autophagy and apoptosis hamper myotube formation and muscle regeneration [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Double immunofluorescence staining for CDK5RAP3 and calnexin (a calcium‐binding protein located on the endoplasmic reticulum membrane) showed that part of the CDK5RAP3 protein was located in the endoplasmic reticulum (Figure S3A). There are multiple inseparable links between apoptosis and autophagy 40,41 . Lyso‐Tracker Red was used to stain lysosomes in living cells.…”
Section: Resultsmentioning
confidence: 99%
“…There are multiple inseparable links between apoptosis and autophagy. 40,41 Lyso-Tracker Red was used to stain lysosomes in living cells. As results shown in Figure 7A, CDK5RAP3 deficiency forced the fluorescence brightness to increase, and it is more concentrated around the cytoplasm near the nucleus compared with the EtOH group (lysosomes are evenly distributed in the cytoplasm).…”
Section: Cdk5rap3 Deficiency Regulated Mtor Pathway and Lead Autophagymentioning
confidence: 99%
“…The crosstalk between apoptosis and autophagy is important in cellular metabolic survival and cellular housekeeping mechanisms [ 46 , 47 , 48 ]. It has been reported that modulating the autophagy of osteoblasts could avoid oxidative damage and allow cells to continue normal function through the endoplasmic reticulum stress pathway [ 49 ].…”
Section: Discussionmentioning
confidence: 99%